Molecular markers as support to plant breeding - Pérez Almeida, Iris Betzaida (2020)
Molecular markers are DNA sequences that can be used to detect genetic variations associated with economically important traits in agriculture, so that they can be used by plant breeders as selection tools, increasing the efficiency of the traditional process, since the genotype of morphologically similar individuals excluding the influence of the environment. Molecular markers have been identified as a useful tool in the selection of superior genotypes; they have been used extensively in gene mapping, both for qualitative and quantitative traits and are also useful, to identify economically important traits in the breeding population and their subsequent manipulation in a short time. Plant breeding through marker assisted selection (MAS) has enormous potential to improve the efficiency of conventional methods. Agricultural biotechnology allows establishing an approximation between the phenotype and the genotype of individuals, allowing the study of the existing variability in genetic materials and sustained progress in the genetic improvement of plants. The advantages of the different available forms of molecular markers and their applications are explored.